Industrial training report: Sabah Electricity. Special project: Customer satisfaction towards electricity services provider (SESB) in Sabah and how SESB handling pandemic COVID-19 issue throughout its organization / Muhd Arif Akmal Md Tajudin - Md Tajudin, Muhd Arif Akmal (Universiti Teknologi MARA, Sabah, 2020)
In determining the image, success or failure of an organization, the organization must meet the criteria and meet specific needs as a motivation in improving and maintaining the quality of customer service such as understanding customer requirements, work procedures and culture, providing the right facilities, adequate resources, employee attitude and commitment and effective monitoring system However, the true value of customer service and satisfaction lies not in the words contained in the customer's charter, brochures and various advertising methods by the organization, but in their own capabilities and effective implementation by the organization itself.